Analysis, design, and simulation of an axially-partitioned dielectric-loaded bi-frequency MILO - Kumar, A.; Tripathi, P.; Dwivedi, S.; Jain, P.K. (Defense Scientific Information and Documentation Centre, 2021)
In this paper, a bi-frequency magnetically insulated line oscillator (MILO) was proposed and designed. The bi-frequency MILO proposed has two axially partitioned slow-wave interaction structures (SWS) and the second SWS is dielectric-loaded to create the frequency shift in the resonant frequency. The conventional MILO device design methodology was followed along with two SWSs separated by a segregation cavity. The dispersion relation of the dielectric-loaded SWS was calculated using an equivalent circuit approach. Furthermore, the cold analysis was carried out to find the energy stored in the different SWSs to validate the device oscillation frequency. The beam wave interaction behaviour and device RF output performance were investigated through 3D PIC (Particle-in-cell) simulation for typical diode voltage of 550 kV, and current 48 kA, respectively. Simulation results illustrate that the proposed MILO generates RF peak power of ~3.5 GW at frequencies 3.62 GHz and 3.72 GHz. The conversion efficiency of the device was ~13.25%. © 2021, DESIDOC.
Keywords: Bi-frequency; Dielectric loading; High power microwaves; MILO; Slow-wave structure